Deriving stellar parameters from GALANTE photometry: bias and precision. Issue 3 (9th April 2020) - Lorenzo-Gutiérrez, A; Alfaro, E J; Maíz Apellániz, J; Barbá, R H; Marín-Franch, A; Ederoclite, A; Cristóbal-Hornillos, D; Varela, J; Vázquez Ramió, H; Cenarro, A J; Lennon, D J; García-Lario, P; et al.
ABSTRACT: In this paper, we analyse how to extract the physical properties from the GALANTE photometry of a stellar sample. We propose a direct comparison between the observational colours (photometric bands normalized to the 515 nm central wavelength) and the synthetic colours derived from different stellar libraries. We use the reduced χ 2 as the figure of merit for selecting the best fitting between both colour sets. The synthetic colours of the Next Generation Spectral Library (NGSL) provide a valuable sample for testing the uncertainty and precision of the stellar parameters derived from observational data. Reddening, as an extrinsic stellar physical parameter becomes a crucial variable for accounting for the errors and bias in the derived estimates: the higher the reddenings, the larger the errors and uncertainties in the derived parameters. NGSL colours also enable us to compare different theoretical stellar libraries for the same set of physical parameters, where we see how different catalogues of models can provide very different solutions in a, sometimes, non-linear way. This peculiar behaviour makes us to be cautious with the derived physical parameters obtained from GALANTE photometry without previous detailed knowledge of the theoretical libraries used to this end. In addition, we carry out the experiment of deriving physical stellar parameters from some theoretical libraries, using some other libraries as observational data. In particular, we use the Kurucz and Coelho libraries, as input observational data, to derive stellar parameters from Coelho + TLUSTY and Kurucz + TLUSTY stellar libraries, respectively, for different photometric errors and colour excesses.